Thymol quantitative analysis in medicinal formulation types through employing of nano-technology and antimicrobial activity in some pathogenic bacterial isolates - MOHAMMED HASAN BARRAK; mohauman majeed; zahraa yosif MOTAWEQ (Smujo International, 2021)
Abstract. Barrak MH, AL-Rufaie MM, Motaweq ZY. 2021. Thymol quantitative analysis in medicinal formulation types through employing nano-technology and antimicrobial activity in some pathogenic bacterial isolates. Nusantara Bioscience 13: 129-137. This study included a method for estimating thymol (THY) in its pure state and in some of its pharmaceutical preparations that were quick, easy, and sensitive, This method is based on nanoparticles that have been modified by oxidation and reduction reactions, In a sodium hydroxide base medium, with polyvinylpyrrolidone as a stabilizer. The thymol drug works as a reducing agent to dilute the ore mineral salt from silver nitrate (Ag+) to silver nanoparticles; the oxidation-reduction reaction product for thymol has the highest absorption at 410 nm. The calibration curve was calculated, and the following information was determined, indicating that the Beer-Lambert Law was followed within the focus range of 0.25 to 50 parts per million. Sandal's sensitivity was 0.052 ?g/cm2, his molar absorptivity was 2.2883 x 103 L / mol.cm, his standard deviation rate was 0.402%, and his correlation coefficient was 0.9989. The biological effect on a number of Gram-negative and Gram-positive bacteria was studied, and the findings showed that the samples prepared were effective against these bacteria.